Unveiling the magnetic and optical properties of barium bismuthate thin films with distinct Ba/Bi ratios - Acero, G. [UNESP]; Ponce, M. A.; Moura, F.; Simões, A. Z. [UNESP] (Elsevier, 2024)
This research aims to investigate the optical and magnetic properties of BaBiO3 (80:20), BaBiO3 (50:50), and BaBiO3 (30:70) thin films obtained by the polymeric precursor method. For better sample designations, the following codes were employed: (80:20) (BBO82), (50:50) (BBO55), and (30:70) (BBO37). The observed properties for barium bismuthates thin films were elucidated in terms of bismuth and oxygen vacancies as well as grain morphology, which can be controlled by stoichiometric changes (Ba/Bi ratios). According to the x-ray results the films crystallize in a rhombohedral BaBiO3 structure with an R-3R space group without any secondary phase as confirmed by Rietveld analyses. According to the photoluminescence results, x-ray photoelectron spectroscopy measurements as well as the law of approach to saturation (LAS), there are a significant presence of oxygen vacancies and vacancy clusters [BiO5.Vo.] in the films with high proportion of bismuth. The optical and magnetic properties developed by these films are originated from the following factors: tilting of BiO6 clusters which changes the length and angle of Bi–O–Bi bonds, creating a magnetic field responsible for the distinct Mr/Ms ratios, the formation of bipolarons caused by charge transfer between [BiO6] and [BiO5. Vo⋅] due to the oxygen vacancies formation, plate-like morphology which makes the domains easier to be switched under an applied external field resulting in a superparamagnetic behavior, charge disproportionation of various valence states (Bi+3 and Bi+5). Based on these results, new potential devices can emerge as possible tools to be applied in switches, actuators, spintronics, magnetic field sensors, etc.
Keywords: BaBiO3; Chemical synthesis; Magnetism; Photoluminescence; Thin films